Leadership Strategy of State University Public Service Agency to Increasing Organizational Performance in Indonesia - Jimad, Habibullah; Maarif, M. Syamsul; Affandi, M. Joko; Sukmawati, Anggarini (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2020)
The purpose of this study was to analyze the leadership strategy of the State University Public Service AgencyÂ in improving the performance of institutions in Indonesia. The study was conducted at three State University Public Service AgencyÂ in Indonesia on regional considerations and ranking of State University Public Service Agency institutions version ofÂ The Ministry of Research, Technology and State University (MoRHE) for 2015-2017, namely the University of Lampung (West Region), Sebeles Maret University (Central Region) and Gorontalo State University (Eastern Region). Leadership strategy as an effort to improve the performance of institutions of State University Public Service Agency involves twelve experts, namely the highest leader (Rector), Vice Rector, Dean and Chair of the Institute for at least one period (four years). Development of strategies using Analytical Hierarchy Process (AHP). Leadership strategy of State University Public Service Agency can be implemented by integrating the leader selection system, leadership development and leadership performance evaluation. The performance measures include graduate quality, publication quality, innovation quality, student quality and service quality.